Internalization of the Values Al-Karimah Ahklaq Education in NU Fatayat Activities Millennial Generation - Rukhmana, Hidayatur; Mispani, Mispani; Jannah, Siti Roudhotul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Fatayat Nahdlatul Ulama (Fatayat NU) is a women’s organization affiliated with Nahdlatul Ulama (NU), the largest Islamic organization in Indonesia. As an integral part of NU, Fatayat NU plays a significant role in promoting Islamic teachings, particularly the values of akhlakul karimah (noble character), in a manner that is easily understood and accepted by the community. The organization achieves this not only through educational activities but also by setting moral examples through its leaders. This study employs a qualitative field research approach, utilizing descriptive data obtained from written and verbal expressions of informants as well as observed behaviors within their social context. The research aims to explore how the values of akhlakul karimah education are internalized through Fatayat NU’s activities among the millennial generation in Sumber Rejo Village, Kota Gajah District, Central Lampung. The informants consist of the head and members of the Fatayat NU Sumber Rejo branch, along with the head of Sumber Rejo Village. Data were collected through observation, interviews, and documentation. The findings reveal that the internalization of akhlakul karimah values among Fatayat NU members is carried out through various religious and educational activities, including the study of Taysirul Kholaq, regular Yasinan recitations, Qur’an study sessions, quarterly religious gatherings, and manaqiban (commemorations of saints). These activities serve as an effective means to convey Islamic moral teachings to millennial women, enabling them to apply these values in their daily lives.